Implementasi Media Pembelajaran Poster untuk Meningkatkan Hasil Belajar pada Pembelajaran Ilmu Pengetahuan Alam (IPA) Kelas IV di MIS Al-Irsyadiyah - Amaira Utami; Nurpatia (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
ABSTRACT This study aims to determine the effect of implementing the poster as learning media on students' learning outcomes in 4th grade of MIS Al-Irsyadiyah in science. The research method implements quasi-experimental with one group postest-prettest design. A total of 22 4th-grade students in MIS Al-Irsyadiyah participated in this study as research samples. The data collection techniques in this study implement test instrument that was given as a pretest and posttestt. Moreover, the data analysis technique used a parametric statistical analysis t-test. According to the results, it can be obtained that the tcount 19.193 higher than the result of the ttable 1.68195. Therefore, it can be concluded that the implementation of the poster as learning media in learning science is found to enhance student's learning outcomes.